The Influence Of The Work Environment, Training And Development Of Human Resources On Employee Performance Mediated By Job Satisfaction - Utami Rezky Mayang Sari; Yana Fajriah; Zulfikry Sukarno (International Journal of Education Management and Religion, 2026)
This study aims to analyze the influence of the Work Environment, Training and Development of Human Resources on Employee Performance mediated by Job Satisfaction. The research approach uses a quantitative approach with primary data sources through the distribution of questionnaires to 86 operational marketing employees of PT Bank Central Asia Tbk Makassar Branch as respondents. To measure the direct influence of the Work Environment, Training and Development of Human Resources variables on employee performance and its influence if mediated by the job satisfaction variable, the Structural Equation Model-PLS path analysis tool is used. The results of the study indicate that partially, the variables of Work Environment, Training, and Development of Human Resources have a positive and significant effect on employee performance, while the variable of job satisfaction does not affect employee performance. Furthermore, the variables of Work Environment, Training, and Development of Human Resources also have a positive and significant effect on job satisfaction. Meanwhile, the study found that the indirect effect of the variables of Work Environment, Training, and Development of Human Resources on employee performance, mediated by job satisfaction, is positive and significant.